Mature workers in organisations: Insights from CEPAR's benchmarking survey of the Australian workforce - Petery, Gigi; Andrei, Daniela; Parker, Sharon (2019)
Global population aging trends have led government leaders to ponder effective strategies to reduce costs and maximize engagement associated with older adults. One approach is to encourage organizations to attract, hire, and retain mature-aged workers. However, there is a shortage of evidence-based recommendations to guide organizational scholars and practitioners in effectively managing an aging workforce, and the associated increase in workplace age diversity (Ali & French, 2019; Truxillo, Cadiz, & Hammer, 2015; Zacher & Griffin, 2015). In an effort to address this empirical scarcity, the Australian Research Council has funded, through the Centre of Excellence in Population Ageing Research (CEPAR), the “Mature Workers in Organisations” research stream. As part of this seven-year project, approximately 15 organizations are being recruited for a longitudinal, multi-level study assessing organizational processes and interventions aimed at an aging and age diverse workforce, and in particular ensuring workers’ health, productivity, and ability to provide care. A key element of this project has been the development of a comprehensive survey to be used for diagnosing workplace success and opportunities, and to track changes resulting from organization-driven interventions. As an important first step, this survey is being used to establish benchmarks within Australia; these ratings will later be used to gauge organization-level performance on a variety of indicators. To establish the benchmark ratings, over 2,500 participants age 18 and older are being drawn from Qualtrics panels of Australian working adults to complete a cross-sectional survey consisting of established items that assess employee perceptions of their workplace. These include measures covering a wide variety of topics, such as organization policies and practices, team work, work design, as well as individual attitudes, behaviours and characteristics. Benchmark data collection is currently underway and is expected to be completed by mid-June 2019. Additionally, we are rapidly advancing towards commencing data collection with several of our collaborating, industry-diverse organizations and anticipate having baseline data for at least a few by the end of July 2019. Insights and implications from the benchmark survey will be presented and discussed, including how well Australian employers as a whole are doing at cultivating an age inclusive work environment. If available, organizational case study results will be compared and contrasted against the benchmark data and each other to reveal a more nuanced perspective.